Analytical simulation of HgCdTe photovoltaic detector for long wavelength infrared (LWIR) applications - Saxena P.K.; Chakrabarti P. (My University, 2025)
A generic model of a long-wavelength infrared photodetector based on Hg1-xCdxTe (x=0.22) narrow bandgap semiconductor has been developed to examine the potential of the device for possible application in free space optical communication at 10.6 μm. The dark current analysis of the detector has been carried out by considering all the dominant current components including tunneling. The lifetime of the carriers has been modeled by taking into the account radiative as well as nonradiative recombination processes. The analysis revealed that the current in photodetector under reverse bias is dominated by trap assisted tunneling component of the current which causes a reduction in the quantum efficiency value at low and moderate reverse bias. The noise equivalent power decreases with increase in value of the equivalent load resistance of the receiver circuit. The photodetector exhibits a dark current, I0≈4×10-6A, zero-bias dynamic resistance, R0≈106Ωquantum efficiency, η≈67% at 10.6 μm and noise equivalent power, (NEP)≈10 -13W-Hz1/2.